Recent progress in pneumococcal protein vaccines - Li, Sha; Liang, Hangeri; Zhao, Shui-Hao; Yang, Xiao-Yan; Guo, Zhong (Frontiers in Immunology, 2023)
Pneumococcal infections continue to pose a significant global health concern, necessitating the development of effective vaccines. Despite the progress shown by pneumococcal polysaccharide and conjugate vaccines, their limited coverage and the emergence of non-vaccine serotypes have highlighted the need for alternative approaches. Protein-based pneumococcal vaccines, targeting conserved surface proteins of Streptococcus pneumoniae, have emerged as a promising strategy. In this review, we provide an overview of the advancements made in the development of pneumococcal protein vaccines. We discuss the key protein vaccine candidates, highlight their vaccination results in animal studies, and explore the challenges and future directions in protein-based pneumococcal vaccine.